THE USE OF INTERACTIVE FLAT PANELS IN ELEMENTARY SCHOOL LEARNING AND ITS IMPLICATIONS FOR STUDENTS' DIGITAL LITERACY - Tetty Siska Noviani; Ria Indrawati; Erlisnawati; M. Yogi Riyantama Isjoni; Charlina (SOSIOEDUKASI, 2026)
The digital transformation of learning in Indonesian elementary schools has encouraged the use of Interactive Flat Panels as interactive instructional media. However, the role of this technology in improving students’ digital literacy has not been adequately explained in the existing literature. This article aims to analyze the patterns of Interactive Flat Panel use in elementary schools, identify its impact on learning processes and outcomes, and explain its implications for strengthening students’ digital literacy. This study employs a narrative literature review with thematic synthesis of fourteen core papers covering empirical studies, review studies, elementary digital literacy studies, and conceptual papers on interactive boards. The findings show that the use of Interactive Flat Panels most consistently contributes to increased motivation, engagement, collaboration, and conceptual understanding through visualization, simulation, interactive quizzes, and touchscreen interaction. However, evidence of their direct contribution to improving digital literacy remains limited, as most studies have not specifically measured digital literacy dimensions. The strongest academic contribution of Interactive Flat Panels lies in their function as a pedagogical medium that can support information literacy, media literacy, technical skills, and digital collaboration when integrated through interactive, reflective, and formative assessment-based learning design. Their effectiveness depends on teachers’ TPACK competence, digital content readiness, infrastructure support, and a school culture that encourages innovation. This article emphasizes that strengthening elementary students’ digital literacy through Interactive Flat Panels requires a shift from presentational use toward participatory pedagogical use.